An Analysis of Foreign Cultural Values in an English Textbook: A Study in the English Literature Study Program - Puspitasari, Rianny; Devi, Anit Pranita; Agnyoto, Panji; Rahayu, Sri (Khazanah Sosial, 2026)
This study investigates foreign cultural values in a textbook used in an English Literature Study Program at a private university in Indonesia, focusing on the potential conflicts with Indonesian cultural norms and the perceptions of the lecturer and students towards them. The data were collected through documentation, semi-structured interviews with one lecturer and nine students, as well as a focus group discussion. The result of the analysis reveals several categories of foreign cultural values that contrast with Indonesian norms, including social relations and lifestyle (e.g., open dating and party culture), politeness and norms (e.g., revealing clothing), everyday habits (e.g., gambling), religious references (e.g., Taoism), and worldview (e.g., direct expressions of hatred). Nevertheless, although these contents sometimes contradict Indonesian local values, the respondents acknowledged their value in enhancing their vocabulary, idiomatic competence, and contextual language understanding. The lecturer and students highlighted the importance of clarification and discussion to compare the differences between the target language culture and local culture, with the lecturer playing a crucial role in encouraging reflection. It was also found that the students demonstrated cultural filtering in accepting or rejecting foreign values based on several aspects, including religions, social norms, and family values. The study outlines that foreign cultural values in EFL materials should not be viewed as threats but as opportunities for cross-cultural understanding.